Analysis of the metals and metalloids concentrations and of the bacterial population in sediments of the Red River Delta, Vietnam - Chifflet, Sandrine; Chu van, Thuoc; Bui Van, Vuong; Pham The, Thu; Mari, Xavier; Pradel, Nathalie (Frontiers in Microbiology, 2024)
In this study, we discuss for the first time the relationships between the diversity of the bacterial population and of the metals and metalloids concentrations in the sediments of the Red River Delta, Vietnam. The analysis of the 16S rRNA by the Illumina technology revealed a diversified population and a potential of bioremediation by the microorganisms, notably by the Bacilli relatively abundant in the Bach Dang estuary, where high metals and metalloids concentrations were highlighted. This work offers new information on the environmental context of the delta and highlights the potential impact that metals and metalloids may have on the bacterial population. Further investigations on the role of the bacteria in the biogeochemistry of this ecosystem will be of interest for the development of bioremediation processes.